2013
DOI: 10.1021/nn305341x
|View full text |Cite
|
Sign up to set email alerts
|

Improved Quantum Efficiency of Highly Efficient Perovskite BaSnO3-Based Dye-Sensitized Solar Cells

Abstract: Ternary oxides are potential candidates as an electron-transporting material that can replace TiO₂ in dye-sensitized solar cells (DSSCs), as their electronic/optical properties can be easily controlled by manipulating the composition and/or by doping. Here, we report a new highly efficient DSSC using perovskite BaSnO₃ (BSO) nanoparticles. In addition, the effects of a TiCl₄ treatment on the physical, chemical, and photovoltaic properties of the BSO-based DSSCs are investigated. The TiCl₄ treatment was found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(90 citation statements)
references
References 49 publications
(84 reference statements)
1
89
0
Order By: Relevance
“…The binding energies of Ti 2p 3/2 (458.6 eV) and Ti 2p 1/2 (464.4 eV) in Fig. 5(a) correspond to Ti 4+ oxidation state, meaning the pure stoichiometric TiO 2 structure [21]. As seen, the Nb-doping causes the peak shift of Ti 2p toward a higher binding energy, which is likely attributed to the larger electronegativity of Nb (1.6) than that of Ti (1.54).…”
Section: Structural Characterization Of Nb-doped Tio 2 Npsmentioning
confidence: 99%
“…The binding energies of Ti 2p 3/2 (458.6 eV) and Ti 2p 1/2 (464.4 eV) in Fig. 5(a) correspond to Ti 4+ oxidation state, meaning the pure stoichiometric TiO 2 structure [21]. As seen, the Nb-doping causes the peak shift of Ti 2p toward a higher binding energy, which is likely attributed to the larger electronegativity of Nb (1.6) than that of Ti (1.54).…”
Section: Structural Characterization Of Nb-doped Tio 2 Npsmentioning
confidence: 99%
“…The peak deconvolution process (inset) clearly shows that O 1s spectrum of the reference is composed of two peaks, at 530.1 and 531.4 eV. The peak with lower binding energy is usually associated with the contribution of O 2À ions in ZnO films, whereas the other one with higher binding energy is probably ascribed to the adsorbed hydroxyl groups (-OH) on the surface [26][27][28]. In addition, a peak at 530.9 eV in insets is observed for the surface modified films that are assigned to the lattice oxygen in the TiO 2 .…”
Section: Surface Modification and Interface Properties Variationmentioning
confidence: 99%
“…On the other hand, there is no substantial reports are available based on ternary metal oxide (TMO) as electron transporting layer (ETL) for PSC. Shin et al reported nano-particulate BaSnO 3 and Zn 2 SnO 4 ternary metal oxides (TMO) for dye sensitized solar cells, and demonstrated 6.2%, 6%, power conversion efficiency (PCE) respectively1920. Moreover, Zn 2 SnO 4 nanoparticles have been used for PSC and demonstrated ~7% PCE21.…”
mentioning
confidence: 99%